Effectiveness of a Nurse-Led Education Program in Childcare Settings: A Systematic Review - Pidjadee, Chakkrich; Soh, Kim Lam; Saidi, Hasni Idayu; Attharos, Tassanee; Soh, Kim Geok; Siricharoenwong, Kanjana (John Wiley and Sons Inc, 2025)
Background: Nurse-led education programs in childcare settings are critical for improving early childhood health outcomes and caregiver practices. Despite their potential, a systematic synthesis of their effectiveness is lacking. Aim: To summarize the characteristics and evaluate the effectiveness of existing nurse-led education programs in childcare settings through a systematic review of experimental studies. Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A comprehensive search was conducted in five databases from inception to December 9, 2024. Two reviewers independently screened articles, extracted data, and assessed study quality. Due to methodological heterogeneity, a narrative synthesis was performed. The review was registered with PROSPERO (CRD42024618983). Results: Twelve studies met the inclusion criteria, involving 900 childcare workers and 920 families. The programs targeted two main areas: prevention of child health issues and management of child health issues. Lectures and group discussions were the most frequently used strategies. Nurses assumed diverse roles, including educators, consultants, and facilitators. The findings revealed several benefits, including reduced rates of upper respiratory illness, improved family health practices—such as appropriate medication use—and enhanced childcare worker competencies in first aid knowledge. Linking Evidence to Action: Nurses play a critical role in implementing education programs in childcare settings. Their contributions should be fully integrated into program planning and delivery. Future research should adopt rigorous methodologies to strengthen evidence-based practices and improve child health outcomes and caregiver competencies.